2023
DOI: 10.1038/s43018-023-00570-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-intrinsic sensitivity to the pro-apoptotic effects of IFN-γ is a major determinant of CD4+ CAR T-cell antitumor activity

Abstract: CD4+ T cells and CD4+ chimeric antigen receptor (CAR) T cells display highly variable antitumor activity in preclinical models and in patients; however, the mechanisms dictating how and when CD4+ T cells promote tumor regression are incompletely understood. With the help of functional intravital imaging, we report that interferon (IFN)-γ production but not perforin-mediated cytotoxicity was the dominant mechanism for tumor elimination by anti-CD19 CD4+ CAR T cells. Mechanistically, mouse or human CD4+ CAR T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 71 publications
2
21
0
Order By: Relevance
“…Activated T cells secrete Interleukin 2 (IL-2), which promotes the proliferation and differentiation of T cells [ 25 , 26 ]. Interferon-γ (IFN-γ) is secreted by activated T cells and exerts anti-tumor effects [ 27 ]. In order to detect the effect of IGFBP3 on Jurkat cells activation, we measured the mRNA expression of IL-2 and IFN-γ in Jurkat cells after co-culture with IGFBP3 overexpressing cells.…”
Section: Resultsmentioning
confidence: 99%
“…Activated T cells secrete Interleukin 2 (IL-2), which promotes the proliferation and differentiation of T cells [ 25 , 26 ]. Interferon-γ (IFN-γ) is secreted by activated T cells and exerts anti-tumor effects [ 27 ]. In order to detect the effect of IGFBP3 on Jurkat cells activation, we measured the mRNA expression of IL-2 and IFN-γ in Jurkat cells after co-culture with IGFBP3 overexpressing cells.…”
Section: Resultsmentioning
confidence: 99%
“…The 10F04mc TCR, which is a type II HLA molecular-restricted TCR, has been transduced into both CD4 + and CD8 + T cells, and both types of T cells have shown functional anti-tumor activity. CD4 + T cells transduced with 10F04mc TCR not only secret cytokines such as IFNγ, TNFα, and IL-2 but also secret high levels of Granzyme B, indicating their potential to exert cytotoxic functions 41 43 . The multifunctional of 10F04 TCR in both CD4 + and CD8 + T cells may explain its superior antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it was further revealed that CD4+T cells, in conjunction with IFN-activated mononuclear phagocytes, collectively instigated an indirect inflammatory process resulting in tumor cell death ( 18 ).. In recent years, CAR-T technology has been used to modify CD4+ T cells, and anti-tumor ability does not depend on cytotoxicity, but indirectly acts on tumor cells through the production of interferon-γ (IFN-γ), a large area and a long distance ( 19 ). In addition, the successful application of Adoptive cell transfer (ACT) immunotherapy with CD4+T cells in clinical research holds immense significance for the prospective treatment of cancer patients, undoubtedly paving the way for advancements in future therapies.…”
Section: Discussionmentioning
confidence: 99%